Study guide to accompany Samuelson-Nordhaus macroeconomics - Miners, Laurence (McGraw-Hill, 1995)
Basic concepts, fundamental concepts of macroeconomics, aggregate supply, economic growth, and macroeconomic policy and international trade and the world economy.